Preparation of phosphorus-bridged iron-nickel monatomic / TiO2-x nanotube array electrode and application of phosphorus-bridged iron-nickel monatomic / TiO2-x nanotube array electrode in advanced treatment of pharmaceutical wastewater

The preparation of P-bridged Fe and Ni single-atom-loaded TiO2-x NTA photoanode materials through template-quenching-exogenous calcination and phosphating method was carried out, which solved the material performance limitations of existing photoelectrocatalytic technologies in degrading antibiotics and resistance genes, and achieved the realization of the material performance limitations of existing photoelectrocatalytic technologies. High-efficiency and low-consumption photoelectric catalytic degradation effect.

CN119455994AActive Publication Date: 2025-02-18NORTH CHINA ELECTRIC POWER UNIV

Patent Information

Application Number
CN202411585817.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-18
Estimated Expiration
2044-11-08

AI Technical Summary

Technical Problem

Existing photoelectrocatalytic technologies have limitations in material performance in degrading antibiotics and resistance genes, including high preparation costs, poor stability and low light utilization, resulting in limited application value.

Method used

The P-bridged Fe and Ni single-atom-loaded TiO2-x NTA (FeNiPx/TiO2-x NTA) photoanode materials were prepared by template-quenching-exogenous calcination phosphating method. By optimizing the single-atom coordination environment and atomic-level interface structure, Activate single-atom d-orbital electrons, enhance the interaction between single-atoms and carriers, and improve catalytic activity and stability.

Benefits of technology

It has achieved efficient and low-consumption photoelectro-catalyzed degradation of antibiotics and resistance genes in wastewater, significantly improving the amount and stability of the active species production of the catalytic system, and reducing the reaction energy barrier in the generation process of active species.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119455994A_ABST
    Figure CN119455994A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of environmental engineering, and discloses preparation of a phosphorus-bridged iron-nickel monatomic / TiO2-x nanotube array electrode and application of the phosphorus-bridged iron-nickel monatomic / TiO2-x nanotube array electrode in advanced treatment of pharmaceutical wastewater. The P-bridged Fe and Ni monatomic loaded TiO2-x NTA photo-anode material is prepared by adopting a template-quenching-exogenous calcination phosphating method. By optimizing and regulating a monatomic coordination environment, an atomic-scale interface structure and a carrier defect state, monatomic d orbital electrons are activated, interaction between monatomic and a carrier is enhanced, and the purpose of improving monatomic catalytic activity and stability is achieved. A photoelectrocatalytic degradation system is constructed on the basis of a FeNiPx / TiO2-x NTA photo-anode, a reaction energy barrier in the active species generation process is reduced through the synergistic effect between single atoms and a substrate, and the generation amount of active species in the system is increased. The material is simple in preparation method and easy for large-scale production, can be directly used in the existing photoelectrochemical device, and can greatly save the transformation and operation cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of environmental engineering technology, and relates to the research on the preparation technology of sub-titanium oxide nanotube array materials by using P-doped double single-atom coordination environment regulation, and particularly relates to the innovation of the method of using the material as a photoanode to construct a photoelectrocatalytic degradation system for deep treatment of medical wastewater. Background Art

[0002] Studies have shown that various types of antibiotics and antibiotic resistance genes have been widely detected in surface water, sewage treatment plant effluent, groundwater and other water sources around the world, with antibiotic concentrations ranging from 1-1670ng / L. Antibiotics inhibit the growth of microorganisms in the environment, induce the reproduction of resistant microorganisms, and act on higher organisms by enriching and amplifying in the body, seriously threatening ecological safety and human health. Since such pollutants are easy to polymerize in water to form polymers with more stable physical and chemical properties, and their own biological toxicity is high, traditional sewage treatment technologies (such as activated sludge method, physical adsorption method, and traditional advanced oxidation method) cannot completely remove them. In contrast, photoelectrocatalysis (PEC) is a pollutant degradation technology that takes into account the advantages of photocatalysis and electrocatalysis. At present, there have been a lot of theoretical research and practical exploration work on the degradation of antibiotics using PEC, but due to the limitations of the performance of catalytic electrode materials, the role of photoelectric synergy in promoting the efficient degradation of pollutants cannot be fully utilized. The photoelectric catalytic materials involved in PEC technology are generally restricted by problems such as high preparation cost, poor stability and low light utilization rate, which reduces their practical application value. Therefore, the development of efficient and low-cost photoelectrocatalytic degradation methods for antibiotics and their resistance genes in wastewater has become a research difficulty in the current field of environmental science and engineering, and has important practical significance for reducing potential ecological risks.

[0003] Single-atom catalysts refer to a new type of catalyst in which metal catalysts are uniformly dispersed on a carrier in the form of single atoms, forming a stable and orderly coordination environment. x The article first proposed the concept of single-atom catalysis and reported single-atom Pt / FeO xAs a catalyst for efficient and selective catalytic oxidation of CO. Since then, single-atom catalysts have quickly become the research frontier in the field of catalysis. Each single atom on the surface of the catalytic material is an independent catalytic active center with an atomic utilization rate close to 100%; the size effect at the atomic level can also effectively change the electronic structure of the catalyst, thereby giving it unique catalytic properties; in addition, compared with nanoparticle catalysts, the catalytic active site structure of the single-atom catalyst is uniform, which can effectively improve the selectivity of the catalytic reaction. However, the high surface energy of the single-atom catalyst makes it easy to agglomerate and deactivate, thereby reducing the catalytic activity of the system. At the same time, its preparation method is complicated and costly. It is necessary to rationally design the microstructure, strengthen the interaction between the single atom and the carrier, improve the catalytic activity and stability of the single-atom catalyst, and expand its practical application in the field of photoelectrocatalysis. In recent years, the research on double single-atom catalytic materials has gradually attracted the attention of researchers. This type of catalytic material can provide two different catalytic sites for catalytic reactions. The interaction between the two is conducive to maintaining the stability of the catalytic site and providing additional reaction sites. However, the poor stability of the coordination environment between the double single atoms has limited the development of this type of catalytic material. Introducing non-metallic atoms with low electronegativity between double single atoms can effectively enhance the stability of the single-atom coordination environment, and at the same time construct an electron migration channel between double single atoms, thereby increasing the activity and stability of the catalytic system. In "Insights into mechanism of Fe-dominated activesites via phosphorus bridging in Fe-Ni bimetal single atom photocatalysts", FeNi bimetallic precursors were mixed with CN, and FeNi double single atoms were anchored on the g-C3N4 surface by ultrasonic crushing and calcination in PH3 atmosphere, and P was introduced as a bridging atom between the double single atoms, which significantly improved the catalytic activity of the Fe site of the catalytic material; Ni, as an electron donor, can inhibit the trend of Fe to migrate to a high valence state and improve the catalytic stability. Repeated test results show that the P-bridged double single atom structure can effectively inhibit the agglomeration of single atoms and the deactivation of valence state increase. Therefore, constructing a reasonable double single atom structure on the surface of a suitable photoelectrocatalytic substrate material can significantly improve the catalytic activity and catalytic stability of the system.

[0004] Defective titanium dioxide nanotube arrays (TiO 2-x NTA) is a type of photoelectrocatalytic material with an orderly arrangement of hollow nanotubes with oxygen vacancies. The oxygen vacancies on its surface can be used to capture single atoms. By optimizing the preparation conditions, a stable single-atom coordination environment can be formed. Therefore, it can be used as an excellent substrate material for loading single-atom catalysts. 2-xNTA surface, and doping P (low electronegative ligand) in the coordination structure, regulating the d orbital outside the single atom nucleus and the atomic-level interface structure between the single atom and the carrier, activating the d orbital electrons of the transition metal atom (increasing the number of unpaired electrons in the d orbital of the metal atom), can optimize the activity of the single atom catalyst from the atomic scale. 2-x NTA lattice substitution of O and Ti 3+ connection, forming electron-rich Ti 3+ Center to further improve the photoelectrocatalytic activity and stability of catalytic materials.

[0005] Therefore, the present invention adopts the template-quenching-exogenous calcination phosphating method to prepare P-bridged Fe and Ni single-atom loaded TiO 2-x NTA(FeNiP x / TiO 2-x NTA) photoanode materials. By optimizing the preparation conditions to regulate the single-atom coordination environment, atomic-level interface structure and carrier defect states, the single-atom d orbital electrons are activated and the interaction between the single atom and the carrier is enhanced, so as to improve the single-atom catalytic activity and stability. x / TiO 2-x The NTA photoanode constructs a photoelectrocatalytic degradation system, using the synergistic effect between single atoms and substrates to reduce the reaction energy barrier of the active species generation process and increase the amount of active species generated in the system, achieving the goal of efficient and low-cost photoelectrocatalytic degradation of antibiotics and resistance genes in wastewater. Summary of the invention

[0006] The introduction of low electronegative ligand P can reduce surface energy and enhance structural stability while maintaining a high atomic utilization rate of metal single-atom catalytic materials, effectively inhibiting catalyst agglomeration and oxidative deactivation. The present invention provides a template-quenching-exogenous calcination phosphating method for preparing P-bridged single-atom Fe and Ni photoelectrocatalytic materials. By designing and optimizing the P-bridging structure between single atoms and carriers, a stable single-atom coordination environment and electron-rich single-atom reaction centers are constructed. In this process, how the P-bridging effect regulates the overall electronic structure of the material, activates the d-orbital electrons of Fe and Ni single atoms, and increases the single-atom catalytic activity. The Fe / Ni-P-Ti atomic-level interface formed by P bridging realizes the synergistic reduction of the energy barrier of active species between single atoms and carriers through the proximity effect (the carrier produces a catalytic effect on the single-atom active center connected to it), improves its yield, and strengthens the system's ability to degrade organic pollutants.

[0007] The technical solution of the present invention:

[0008] A phosphorus-bridged iron-nickel single atom / TiO 2-x The preparation method of the nanotube array electrode comprises the following steps:

[0009] Step 1: Select iron nitrate, nickel nitrate, urea and polyvinyl pyrrolidone as reaction precursors to prepare iron-nickel double hydroxide (FeNi(OH) x ); wherein the molar ratio of ferric nitrate to nickel nitrate is 2:1-1:2, the molar amount of urea added is the sum of the molar amounts of ferric nitrate and nickel nitrate added, the amount of polyvinyl pyrrolidone added is 100-500 mg / L, and at the same time, the concentration of ferric nitrate is controlled to be in the range of 0.05-0.5 mol / L; the hydrothermal reaction temperature is 120-160°C, and the reaction time is 6-24h; after the reaction is completed, it is naturally cooled to room temperature, the hydrothermal reactor is taken out, centrifuged to obtain a precipitate, and the precipitate is alternately washed with deionized water and ethanol and centrifuged, and the process is repeated for multiple times until the pH of the supernatant after centrifugation is 7-8, and the obtained solid material is placed in a blast oven and dried at 60°C to obtain FeNi(OH) x ;

[0010] Step 2: Refer to "Unraveling the reinforced photoelectrocatalytic activity and stability via unique configuration of P 3+ -O v -Ti 3+ in TiO 2-x The electro-etching solution configuration method in the article "nanotube array" is to place the titanium mesh as the anode in the electrochemical etching reactor, and the cathode is the lead oxide electrode of the same size, which is placed on both sides of the titanium mesh, with an electrode spacing of 3-8cm, a constant voltage of 25-40V, and run for 1-3h. The reaction is controlled by an ice bath at a temperature of 15-20℃. After the reaction, the titanium mesh is taken out and placed in deionized water. The surface organic solvent and inorganic salt are removed by ultrasound for 2min, and then placed in an oven at 60℃ for drying; the dried titanium mesh electrode is placed in a muffle furnace, the heating rate is 5℃ / min, and the reaction is carried out at a constant temperature of 450℃ for 2h; then, electrochemical reduction is carried out, using it as the cathode and lead oxide as the anode, using 5-10wt% ammonium sulfate aqueous solution as the electrolyte, and the constant current is 1-3mA / cm 2 , electrochemical reduction for 5 to 10 minutes to obtain TiO 2-x Nanoarray (TiO 2-x NTA) electrode;

[0011] Step 3: Prepare the FeNi(OH) x As a hard template material dispersed in the solvent, TiO 2-x NTA is used as a carrier and the hard template material is fixed on the carrier surface by quenching method; among them, FeNi(OH) xThe concentration of the dispersion is 1-20 mg / L; the solvent used for dispersion can be deionized water, anhydrous ethanol, ethylene glycol, FeNi(OH) x The TiO 2-x NTA is heated on a flat heater at a temperature of 300-450°C. In a N2 atmosphere, the TiO 2-x The NTA electrode was placed in the dispersion solution for 10-30 seconds, then taken out and washed in deionized water, and the electrode was dried with cold air to obtain FeNi(OH) x Loaded TiO 2-x NTA;

[0012] Step 4: FeNi(OH) x Loaded TiO 2-x NTA is placed in the downwind direction of the tube furnace, and sodium hypophosphite (sodium hypophosphite is added 1-5g per 100 square centimeters of electrode surface area) is placed in the upwind direction of the tube furnace 5cm away from the electrode, and calcined in a gradient temperature rise under N2 atmosphere; the heating rate is 3-10℃ / min, and the temperature is maintained at 300℃ and 450℃ for 1-2h during the heating process; after calcination, it is naturally cooled to room temperature, the electrode sheet is taken out and used as the cathode, lead oxide is used as the anode, and 5-10wt% ammonium sulfate aqueous solution is used as the electrolyte, and the constant current is 3-5mA / cm 2 , electrochemical reduction for 5-10 min, to obtain P-bridged Fe and Ni single-atom-loaded TiO 2-x NTA(FeNiP x / TiO 2-x NTA) photoanode materials.

[0013] FeNiP x / TiO 2-x NTA was used as the photoanode and titanium mesh as the cathode. The electrode spacing was 1-2 cm. A flow-through photoelectrochemical reaction system was constructed. The wavelength range of the light source was 420-780 nm. The distance between the light source and the electrode was 5-10 cm. The system was operated in a constant current mode with a current density of 1-15 mA / cm 2 . Continuous degradation tests were carried out using simulated wastewater containing 100μg / L-20mg / L concentrations of amoxicillin, levofloxacin, and sulfamethazine, as well as actual pharmaceutical wastewater containing the above pollutants (COD range 200-2000mg / L) as target water bodies. During the 200h reaction, the removal rate of target pollutants in the effluent was maintained at more than 93%. At the same time, for the actual pharmaceutical wastewater, the COD removal rate was more than 66%.

[0014] Beneficial effects of the present invention: The present invention adopts the template-quenching-exogenous calcination phosphating method to prepare P-bridged Fe and Ni single-atom loaded TiO 2-x NTA(FeNiP x / TiO 2-x In step 1, a hard template iron-nickel double hydroxide is prepared, and the hydrothermal process conditions are regulated to form a single-layer or few-layer structure of the iron-nickel double hydroxide, which is beneficial to the stability of the hard template loading during the quenching process. In step 3, the hard template is fixed on the TiO 2-x On the NTA surface, different dispersing solvents can effectively control the oxygen vacancy structure arrangement on the substrate surface during the quenching process. Compared with traditional loading methods such as hydrothermal and electrodeposition, the quenching method can complete the loading process in a shorter time and cause less damage to the substrate structure; the traditional loading method has a poor anchoring effect on TiO 2-x The stability of the NTA structure will be greatly affected, and a uniform single-atom anchoring structure cannot be achieved. In step 4, the in-situ phosphating calcination process uses PH3 to etch the hard template to form a stable Fe and Ni double single-atom structure (such as the attached Figure 1 At the same time, the bridge structure formed between the two single atoms after the introduction of P can regulate the coordination environment of Fe and Ni single atoms, the interface electric field between single atoms and the carrier, and the TiO2 lattice defect structure (metastable Ti 3 + The proximity effect formed by the Fe / Ni-P-Ti interface structure can enhance the interaction between single atoms and the support, improve the electron migration ability and active site stability of the catalytic system. x / TiO 2-x In the NTA photoelectrocatalytic system, due to the high current density, electrocatalysis plays a leading role in the degradation process, and the main active species is ·OH. The active species (superoxide radicals, photogenerated electrons, and photogenerated holes) generated by photocatalysis can regulate the intermediate product conversion path during the pollutant degradation process and increase the TOC elimination rate. In this system, the synergistic effect of single atoms and carriers can enhance the adsorption of water molecules at active sites, reduce the reaction energy barrier of water molecules to ·OH, increase the ·OH generation rate, and achieve deep treatment of difficult-to-degrade pollutants in pharmaceutical wastewater. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 FeNiP x / TiO 2-x STEM image of NTA. DETAILED DESCRIPTION

[0016] The specific implementation of the present invention is described in detail below in conjunction with the technical scheme and the accompanying drawings.

[0017] Example 1

[0018] FeNiP x / TiO 2-x NTA electrode material preparation:

[0019] Iron nitrate, nickel nitrate, urea and polyvinyl pyrrolidone were selected as reaction precursors to prepare iron-nickel double hydroxide (FeNi(OH) x ). Among them, the molar ratio of ferric nitrate and nickel nitrate is 2:1, the molar amount of urea added is the sum of the molar amounts of ferric nitrate and nickel nitrate, the amount of polyvinyl pyrrolidone added is 100 mg / L, and the concentration range of ferric nitrate aqueous solution is 0.1 mol / L. The hydrothermal reaction stability range is 140°C, and the reaction time is 24h. After the reaction is completed, it is naturally cooled to room temperature, the hydrothermal reactor is taken out, and the precipitate is obtained by centrifugation. Deionized water and ethanol are used to wash / centrifuge alternately, and the process is repeated many times until the pH of the supernatant after centrifugation is ~7. The obtained solid material is placed in a blast oven and dried at 60°C. FeNi(OH) x .

[0020] Reference "Unraveling the reinforced photoelectrocatalytic activity andstability via unique configuration of P 3+ -O v -Ti 3+ in TiO 2-x The specific configuration method of the electro-etching solution in the article "nanotube array" is as follows: ethylene glycol, ammonium fluoride and water are added to a beaker in a mass ratio of 93:5:2, and magnetic stirring is performed for 30 minutes to fully dissolve and disperse the ammonium fluoride to obtain an electro-etching solution. The titanium mesh is used as the anode and placed in an electrochemical etching reactor. The cathode is a lead oxide electrode of the same size, which is placed on both sides of the titanium mesh electrode, with an electrode spacing of 5 cm. The constant voltage is 30V, and the operation is 3h. The reaction is controlled by an ice bath to control the temperature of the etching solution within the range of 15°C. After the reaction, the titanium mesh electrode is taken out and placed in deionized water. The surface organic solvent and inorganic salt are removed by ultrasound for 2min, and then placed in an oven at 60°C for drying. The dried titanium mesh electrode is placed in a muffle furnace, the heating rate is 5°C / min, and the reaction is carried out at a constant temperature of 450°C for 2h. After that, electrochemical reduction is carried out, using it as the cathode, lead oxide as the anode, 10%wt ammonium sulfate aqueous solution as the electrolyte, and a constant current of 3mA / cm 2 , electrochemical reduction for 10 min, TiO 2-x Nanoarray (TiO 2-x NTA) electrode.

[0021] The prepared FeNi(OH)x As a hard template material dispersed in the solution, TiO 2-x NTA is used as a carrier and the hard template material is fixed on the carrier surface by quenching method. x The concentration of the dispersion was 5 mg / L, deionized water was selected as the dispersion solvent, FeNi(OH) x Ultrasonication was performed for 60 min to achieve uniform dispersion in the dispersion solvent. During the quenching process, the dispersion was maintained at 4 °C and TiO 2-x NTA was heated on a flat heater at 400°C. After heating for 2 min, TiO 2-x The NTA electrode was placed in the dispersion for 10 seconds, taken out and washed in deionized water, and the electrode was dried with cold air to obtain FeNi(OH) x Loaded TiO 2-x NTA.

[0022] FeNi(OH) x Loaded TiO 2-x NTA was placed in the downwind direction of the tube furnace, and 0.5g of sodium hydrogen phosphite was placed in the upwind direction of the tube furnace 5cm away from the electrode. In the N2 atmosphere, the temperature was gradually increased and calcined. The heating rate was 5℃ / min, and the temperature was maintained at 300℃ and 450℃ for 1h during the heating process. After calcination, it was naturally cooled to room temperature, and the electrode sheet was taken out and used as the cathode, lead oxide as the anode, and 10wt% ammonium sulfate aqueous solution was used as the electrolyte. The constant current was 3mA / cm 2 , electrochemical reduction for 10 min, to obtain P-bridged Fe and Ni single-atom-loaded TiO 2-x NTA(FeNiP x / TiO 2-x NTA-30-3) photoanode material.

[0023] A series of FeNiP were prepared by changing the electrochemical etching time to 1 and 2 h using the above method. x / TiO 2-x NTA electrode material (named FeNiP x / TiO 2-x NTA-30-1, FeNiP x / TiO 2-x NTA-30-2) was used for subsequent performance comparison tests.

[0024] Example 2

[0025] Typical simulated pharmaceutical wastewater degradation test in photoelectrochemical system:

[0026] The FeNiP obtained in Example 1 x / TiO 2-xNTA series materials are used as photoanode, titanium mesh is used as cathode, and the electrode spacing is 1 cm. A flow-through photoelectrochemical reaction system is constructed. The wavelength range of the light source is 420-780nm, and the distance between the light source and the electrode is 5 cm. The system is operated in a constant current mode with a current density of 5 mA / cm 2 . The simulated wastewater containing 20 mg / L amoxicillin was used as the target water body for continuous degradation test. During the reaction period of 12 hours, the reaction water was taken once every 60 minutes. The reaction water was filtered with a 0.22μm water membrane and 2 mL was taken and put into a liquid phase vial. After being collected, it was used to test the degradation performance. After the reaction was completed, 20 mL of the reaction water was taken and filtered with a 0.22μm water membrane as the TOC test sample.

[0027] The concentration of amoxicillin was determined by ultra-high performance liquid chromatography. The test results showed that the series of FeNiP x / TiO 2-x NTA electrode materials can achieve a removal rate of more than 90% for amoxicillin. x / TiO 2-x NTA-30-3 can reach 99%, which is better than other catalytic materials. x / TiO 2-x NTA-30-1, FeNiP x / TiO 2-x NTA-30-2 and FeNiP x / TiO 2-x The TOC removal rates of NTA-30-3 effluent were 36%, 54% and 77% respectively. x / TiO 2-x NTA-30-3 was used as the photoanode material for subsequent photoelectrocatalytic performance testing.

[0028] Comparative Example 1:

[0029] According to the operating conditions in Example 2, only the light source irradiation condition is cancelled and FeNiP is tested. x / TiO 2-x The pure electrocatalytic degradation performance of NTA series materials shows that FeNiP x / TiO 2-x NTA-30-1, FeNiP x / TiO 2-x NTA-30-2, FeNiP x / TiO 2-xThe removal rates of amoxicillin by NTA-30-3 electrode material were 76%, 79%, and 78%, respectively, and the removal rates of effluent TOC were 27%, 39%, and 58%, respectively. This shows that the electrocatalytic process plays a leading role in the degradation of target pollutants, and an effective photocatalytic process can significantly improve the mineralization performance of the system for target pollutants.

[0030] Example 3

[0031] Photoelectrochemical system degradation test of simulated pharmaceutical wastewater with different concentrations of amoxicillin:

[0032] FeNiP x / TiO 2-x NTA-30-3 was used as the photoanode and titanium mesh as the cathode. The electrode spacing was 1 cm. A flow-through photoelectrochemical reaction system was constructed. The wavelength range of the light source was 420-780 nm. The distance between the light source and the electrode was 5 cm. The system was operated in a constant current mode with a current density of 5 mA / cm 2 . The simulated wastewater containing 0.01, 0.1, 1, and 10 mg / L amoxicillin was used as the target water body for continuous degradation test. During the reaction period of 12 hours, the reaction water was taken once every 60 minutes. The reaction water was filtered with a 0.22μm water membrane and 2 mL was taken and put into a liquid phase vial. After being collected, it was used to test the degradation performance. After the reaction was completed, 20 mL of the reaction water was taken and filtered with a 0.22μm water membrane as the TOC test sample.

[0033] The concentration of amoxicillin was determined by ultra-high performance liquid chromatography, and the test results showed that FeNiP x / TiO 2-x The removal rate of NTA-30-3 material for 0.1, 1, 10 mg / L amoxicillin can reach more than 99%; the removal rate of 0.01 mg / L amoxicillin can reach more than 80%. The TOC removal rates of the simulated wastewater with amoxicillin concentrations of 0.01, 0.1, 1, 10 mg / L were 22%, 27%, 79%, and 89%, respectively. This shows that with the degradation of the target concentration, the TOC removal rate and degradation rate both show a downward trend.

[0034] Example 4

[0035] Photoelectrochemical system degradation test of different types of simulated pharmaceutical wastewater:

[0036] FeNiP x / TiO 2-x NTA-30-3 was used as the photoanode and titanium mesh as the cathode. The electrode spacing was 1 cm. A flow-through photoelectrochemical reaction system was constructed. The wavelength range of the light source was 420-780 nm. The distance between the light source and the electrode was 5 cm. The system was operated in a constant current mode with a current density of 5 mA / cm2 . The simulated wastewater containing 20 mg / L levofloxacin and sulfamethazine was used as the target water body for continuous degradation test. The reaction time was 24 hours, and the reaction water was taken once every 60 minutes. The reaction water was filtered with a 0.22μm water membrane and 2 mL was taken and put into a liquid phase vial. After being collected, it was used to test the degradation performance. After the reaction was completed, another 20 mL of the reaction water was taken and filtered with a 0.22μm water membrane as a TOC test sample.

[0037] The concentrations of levofloxacin and sulfadimethoxine were determined by ultra-high performance liquid chromatography. The test results showed that FeNiP x / TiO 2-x The removal rates of levofloxacin and sulfamethazine by NTA-30-3 photoanode were both 99%, and the TOC removal rates were 83% and 76%, respectively. This indicates that the photoanode has a high degradation performance for typical pharmaceutical pollutants in pharmaceutical wastewater.

[0038] Example 5

[0039] Photoelectrochemical system for actual pharmaceutical wastewater degradation test:

[0040] FeNiP x / TiO 2-x NTA-30-3 was used as the photoanode and titanium mesh as the cathode. The electrode spacing was 1 cm. A flow-through photoelectrochemical reaction system was constructed. The wavelength range of the light source was 420-780 nm. The distance between the light source and the electrode was 5 cm. The system was operated in a constant current mode with a current density of 15 mA / cm 2 Actual pharmaceutical wastewater from different processes (COD of 500, 1000, and 2000 mg / L, respectively) was used as the target water body for continuous degradation test. The reaction time was 200 h, and the reaction effluent was taken once every 4 h. The taken reaction effluent was directly put into a 10 mL centrifuge tube and collected uniformly for testing COD removal performance.

[0041] The national standard method was used to test the effluent COD. The test results showed that FeNiP x / TiO 2-x The removal rates of COD of actual pharmaceutical wastewater by NTA-30-3 electrode were 80%, 73% and 65% respectively, which showed that the photoanode had high removal performance for antibiotics and other refractory organic matter in actual pharmaceutical wastewater, and the degradation performance was stable.

Claims

1. A phosphorus-bridged iron-nickel single atom / TiO 2-x A method for preparing a nanotube array electrode, characterized in that: Here are the steps: Step 1: Select iron nitrate, nickel nitrate, urea and polyvinyl pyrrolidone as reaction precursors to prepare iron-nickel double hydroxide (FeNi(OH) x ); wherein the molar ratio of ferric nitrate to nickel nitrate is 2:1-1:2, the molar amount of urea added is the sum of the molar amounts of ferric nitrate and nickel nitrate added, the amount of polyvinyl pyrrolidone added is 100-500 mg / L, and at the same time, the concentration of ferric nitrate is controlled to be in the range of 0.05-0.5 mol / L; the hydrothermal reaction temperature is 120-160°C, and the reaction time is 6-24h; after the reaction is completed, the reaction kettle is naturally cooled to room temperature, the hydrothermal reaction kettle is taken out, and a precipitate is obtained by centrifugation, and the precipitate is washed alternately with deionized water and ethanol and centrifuged, and the process is repeated for multiple times until the pH value of the supernatant after centrifugation is 7-8, and the obtained solid material is placed in a blast oven and dried to obtain FeNi(OH) x ; Step 2: Prepare the electro-etching solution, place the titanium mesh as the anode in the electrochemical etching reactor, and the cathode is the lead oxide electrode of the same size, which is placed on both sides of the titanium mesh, with an electrode spacing of 3-8cm, a constant voltage of 25-40V, and run for 1-3h. The reaction is controlled by an ice bath to control the temperature of the electro-etching solution to 15-20°C. After the reaction is completed, take out the titanium mesh, put it in deionized water, and ultrasonically remove the organic solvent and inorganic salt on the surface, and then dry it; react the dried titanium mesh at a constant temperature of 450°C for 2h; then, perform electrochemical reduction, use the titanium mesh as the cathode, lead oxide as the anode, 5-10wt% ammonium sulfate aqueous solution as the electrolyte, and a constant current of 1-3mA / cm 2 , electrochemical reduction for 5 to 10 minutes to obtain TiO 2-x Nano-array electrode TiO 2-x NTA; Step 3: Prepare the FeNi(OH) x As a hard template material dispersed in the solvent, TiO 2-x NTA is used as a carrier and the hard template material is fixed on the carrier surface by quenching method; among them, FeNi(OH) x The concentration of the dispersion is 1-20 mg / L. During the quenching process, the dispersion is kept at 4-10°C. 2-x NTA is heated on a flat heater at a temperature of 300-450°C. In a N2 atmosphere, the TiO 2-x The NTA electrode was placed in the dispersion solution for 10-30 seconds, then taken out and washed in deionized water, and the electrode was dried with cold air to obtain FeNi(OH) x Loaded TiO 2-x NTA; Step 4: FeNi(OH) x Loaded TiO 2-x NTA was placed in the downwind direction of the tube furnace, and sodium hypophosphite was placed in the upwind direction of the tube furnace. In the N2 atmosphere, the temperature was gradually increased and calcined. During the heating process, the temperature was maintained at 300°C and 450°C for 1-2 hours respectively. After calcination, the temperature was naturally cooled to room temperature, and the electrode sheet was taken out and used as the cathode, lead oxide as the anode, and 5-10wt% ammonium sulfate aqueous solution was used as the electrolyte. The constant current was 3-5mA / cm 2 , electrochemical reduction for 5-10 min, to obtain P-bridged Fe and Ni single-atom-loaded TiO 2-x NTA photoanode material FeNiP x / TiO 2-x NTA, namely phosphorus-bridged iron-nickel single atom / TiO 2-x Nanotube array electrodes.

2. The preparation method according to claim 1, characterized in that: FeNi(OH) x The solvent used for the dispersion is deionized water, anhydrous ethanol or ethylene glycol, FeNi(OH) x The uniform dispersion in the solvent was achieved by ultrasound for 60 min.

3. The preparation method according to claim 1, characterized in that: Sodium hypophosphite is added at a rate of 1-5 g per 100 square centimeters of electrode surface area, and is placed in the tubular furnace at a position 5 cm away from the electrode in the upwind direction.

4. The preparation method according to claim 1, characterized in that: The temperature used for drying was 60°C.

5. The preparation method according to claim 1, characterized in that: In step 4, the heating rate is 3-10°C / min.

6. The preparation method according to claim 1, characterized in that: The method for preparing the electro-etching solution is as follows: ethylene glycol, ammonium fluoride, and water are mixed in a mass ratio of 93:5:2, and the ammonium fluoride is fully dissolved and dispersed by magnetic stirring to obtain the electro-etching solution.

7. A phosphorus-bridged iron-nickel single atom / TiO 2-x The application of nanotube array electrodes in the deep treatment of pharmaceutical wastewater is characterized by: FeNiP x / TiO 2-x NTA was used as the photoanode and titanium mesh as the cathode. The electrode spacing was 1-2 cm. A flow-through photoelectrochemical reaction system was constructed. The wavelength range of the light source was 420-780 nm. The distance between the light source and the electrode was 5-10 cm. The system was operated in a constant current mode with a current density of 1-15 mA / cm 2 , treating pharmaceutical wastewater.

8. The use according to claim 7, characterized in that: Pharmaceutical wastewater is wastewater containing amoxicillin, levofloxacin and sulfamethazine.

9. The use according to claim 7, characterized in that: The concentration of pharmaceutical wastewater is 100μg / L-20mg / L.

Citation Information

Patent Citations

  • Method of treating pollutants in water body through photoelectric-catalytic reduction

    CN106219687A

  • Titanium dioxide loaded nickel ferrite and graphene oxide composite thin film, preparation method thereof, and application of titanium dioxide loaded nickel ferrite and graphene oxide composite thin film to wastewater treatment

    CN109759065A

  • Preparation method of FeNiP / C@MXene composite negative electrode material for lithium ion battery

    CN112635738A

  • Preparation method and application of Fe and Cu double-monatomic anchored Ti4O7 electrode

    CN115650375A

  • Preparation of titanium black nanotube material with N < 3 + > / P < 3 + >-vacancy-Ti < 3 + > structure and application of titanium black nanotube material in photoelectrocatalytic efficient degradation of organic pollutants

    CN117380239A

Cited By

  • Preparation of titanium black fibrofelt porous electrode regulated by strain strategy and application of titanium black fibrofelt porous electrode in advanced treatment of organic industrial wastewater

    CN120573813A

  • Preparation of phosphorus-doped high-curvature-regulated titanium black porous electrode and application of phosphorus-doped high-curvature-regulated titanium black porous electrode in deep reduction of resistance gene in electrochemical enhanced medical wastewater

    CN120646973A